2017
DOI: 10.1111/cbdd.13009
|View full text |Cite
|
Sign up to set email alerts
|

New thiourea and 1,3‐thiazolidin‐4‐one derivatives effective on the HIV‐1 virus

Abstract: Thiourea derivatives have been reported to possess many biological activities, among them antiviral and antitumoral properties. As part of our continuing effort to develop new active compounds, we report the synthesis and the evaluation of new fifteen thiourea derivatives with 1,3-benzothiazole-2-yl moiety, among them a group of biologically active (1-7) also underwent cyclization to 1,3-thiazolidin-4-ones. Molecular structure of four compounds (4, 13, 15 and 3a) was determined by an X-ray crystallography. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…The (thio)urea branch is an element of several medicines with anticancer profiles, such as sorafenib, multikinase-inhibitory diarylthiorea derivative, or tenovin-1, the benzylthiourea, which acts as a reversible inhibitor of class III HDAC sirtuins (Figure 1). On the other hand, it was reported that (hetero)aryl terminal fragments of thiourea moiety, enriched with electron-negative substituents, could provide biological responses, not only cytotoxic [2][3][4], but also antibacterial [2][3][4][5][6][7][8], antiviral [2,[9][10][11][12], antimycobacterial [5,13], antioxidant [14], and anti-inflammatory [6] properties, as well as central nervous system activation [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The (thio)urea branch is an element of several medicines with anticancer profiles, such as sorafenib, multikinase-inhibitory diarylthiorea derivative, or tenovin-1, the benzylthiourea, which acts as a reversible inhibitor of class III HDAC sirtuins (Figure 1). On the other hand, it was reported that (hetero)aryl terminal fragments of thiourea moiety, enriched with electron-negative substituents, could provide biological responses, not only cytotoxic [2][3][4], but also antibacterial [2][3][4][5][6][7][8], antiviral [2,[9][10][11][12], antimycobacterial [5,13], antioxidant [14], and anti-inflammatory [6] properties, as well as central nervous system activation [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Thiazolidinone belongs to this class and is a versatile scaffold to the development of new bioactive compounds. Numerous studies describe a wide range of pharmacological properties of thiazolidinones: anti-HIV 12 , antitumor 13 , 14 , anti-inflammatory 15 , antimicrobial 16 , antihyperglycemic 17 , and acetyl/butyrylcholinesterase inhibition 5 . Thiazinanones (six-membered heterocycle) also show important biological activity such as anticancer 18 , antimalarial 19 , antihypertensive 20 , antibacterial 21 , and antihyperglycemic 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The thiourea branch represents an important synthon, which is responsible for numerous biological activities, such as antimicrobial, antiviral, antiproliferative, and cytotoxic properties . In addition, the class of (thio)urea derivatives were shown to mediate psychotropic‐like effects in rodents.…”
Section: Introductionmentioning
confidence: 99%